Failure of postural manoeuvres to prevent lumbar puncture headache. - Hilton-Jones, D; Harrad, R; Gill, M; Warlow, C (1982)
Diagnostic lumbar puncture was performed on 76 neurological inpatients. They were randomly allocated to one of four bed rest positions for four hours following the procedure (supine and horizontal, prone and horizontal, supine with head-down tilt and prone with head-down tilt) after which they were allowed to get up. There was no substantial or significant difference in the incidence of headache between the four groups. Expectation of headache did not appear to be an important factor in its development.